Evaluation of a computed-tomography-based assessment scheme in treatment decision-making for isolated orbital floor fractures. Issue 9 (September 2018) - Frohwitter, Gesche; Wimmer, Stephan; Goetz, Carolin; Weitz, Jochen; Ulbig, Michael; Kortuem, Karsten U.; Dangelmaier, Julia; Ritschl, Lucas; Doll, Christian; Ristow, Oliver; Kesting, Marco R.; Koerdt, Steffen
Abstract: Introduction: Treatment decisions for fractures of the orbital floor are based on clinical appearance, ophthalmological examination, and computed tomography (CT) scans. In extensive fractures, decisions are easily made between conservative and surgical treatment. However, objective parameters are rare in inconclusive cases. Materials and methods: Our retrospective study included 106 patients with unilateral isolated orbital floor fractures. Correlations between preoperative ophthalmological examinations and specific CT parameters were performed. Results: The defect size of the fracture appeared to be significantly associated with the presence of diplopia. CT-morphological parameters and preoperative ophthalmological results showed statistical significance for diplopia and incarceration of inferior rectus muscle (IRM), diplopia and displacement of IRM, decreased mobility and incarceration of IRM, and decreased mobility and displacement of IRM. Discussion: Our clinical assessment scheme for CT scans of orbital floor fractures is aimed at facilitating treatment decision making using four CT-based variables. As critical size defects of the orbital floor of ≥2 cm 2 are likely to cause clinically significant posterior displacement of the globe, resulting in enophthalmos, the proposed parameters offer a readily accessible and easy to evaluate scheme that helps to identify patients in need of surgical intervention.